Konsep pendidikan Ki Hadjar Dewantara dan implementasinya di Sekolah Dasar di Indonesia - Harini, Rochmimah; Istiq’faroh, Nurul; Hendratno (Journal of Contemporary Issues in Primary Education, 2023)
This research aims to explore the essence of Ki Hajar Dewantara's educational thinking and its relevance to the world of modern education as an educational pioneer. Ki Hajar Dewantara, or his full name Raden Mas Soewardi Soerjaningrat, is an Indonesian educational figure who has made a major contribution to the development of education in Indonesia. One of the theories he developed was "Young Shoots", which can be applied to learning in early elementary schools. Ki Hadjar Dewantara's thoughts on education have become a distinctive image for the history of education in Indonesia. The educational concept displays the uniqueness of Indonesian culture and emphasizes the importance of processing students' potentials in an integrated manner. This type of research is qualitative research in the form of library research. The collection technique is documentation, document analysis. Verification descriptive data analysis techniques and drawing conclusions. The results of this research are Ki Hajar Dewantara's educational thoughts and their implementation in elementary schools today.